Analysis of suitability and carrying capacity of coastal tourism areas (case study at Sayang Heulang Beach, Garut Regency, West Java) - Heni, Heni; Nurhayati, Atikah; Bachtiar, Eri; Pamungkas, Wahyuniar (Acta Aquatica: Aquatic Sciences Journal, 2022)
Sayang Heulang Beach is a beach tourism area in Garut Regency, West Java. The Garut Regency Government carries out the construction and development of tourist facilities to support tourism activities and add attraction to increase the number of tourists. In the development and construction of tourist areas, it must adapt to the conditions of the surrounding environment so that its sustainability can be maintained. This study aims to analyze the suitability and carrying capacity of the area, as well as to determine the perception of the public and tourists on the condition of the tourist area of Sayang Heulang Beach. This research was conducted in December 2021 - May 2022 in Mancagahar Village, Pameungpeuk District, Garut Regency, West Java. The method used in this study is a survey method in the form of primary data collection including tourism suitability index parameters (depth, beach type, beach width, base material, current speed, water brightness, beach slope, land cover, availability of clean water and hazardous biota) and carrying capacity of the area, the perception of the community and tourists through the provision of questionnaires/questionnaires, as well as direct observation in the field. Secondary data is obtained through literature studies such as data from agencies. The results of this study indicate that the index value of the suitability of beach tourism at Sayang Heulang Beach at 3 points of the research station is 86% which is categorized (S1) very suitable for beach tourism activities. The area's carrying capacity for beach recreational activities at Station I can accommodate 529 people/day, Station II can accommodate 125 people/day, and Station III can accommodate 153 people/day. The perception of the public and tourists in the Sayang Heulang Beach area on the variables of tourism potential and development, facilities and services received a good perception according to the community and quite good according to tourists, while tourist attraction and accessibility received a fairly good perception.Keywords: Area carrying capacity; Beach tourism; perceptions; Public and tourist; Tourism suitability